Biokinetics and clearance of inhaled gold ultrasmall-in-nano architectures. Issue 9 (4th August 2020) - Mapanao, Ana Katrina; Giannone, Giulia; Summa, Maria; Ermini, Maria Laura; Zamborlin, Agata; Santi, Melissa; Cassano, Domenico; Bertorelli, Rosalia; Voliani, Valerio
Abstract : After inhalation, ultrasmall-in-nano gold architectures accumulate in the lungs, reach secondary organs, and are excreted, encouraging the clinical translation of plasmonic nanomaterials to the management of cancer and infectious diseases. Abstract : Among an organism's entry portals, the respiratory tract is one of the most promising routes for non-invasive administration of therapeutics for local and systemic delivery. On the other hand, it is the subtlest to protect from environmental pollution and microbial occurrences. Here, the biokinetics, distribution, and clearance trends of gold ultrasmall-in-nano architectures administered through a single intranasal application have been quantitatively evaluated. Apart from reaching the lung parenchyma, the (bio)degradable nano-architectures are able to translocate as well to secondary organs and be almost completely excreted within 10 days. These findings further support the clinical relevance of plasmonic nanomaterials for oncology and infectious disease treatment and management. Notably, this investigation also provides crucial information regarding the associated risks as a consequence of the pulmonary delivery of nanoparticles.